2019
DOI: 10.1093/infdis/jiz082
|View full text |Cite
|
Sign up to set email alerts
|

The Syndrome We Agreed to Call Bronchiolitis

Abstract: We are ignoring evidence suggesting that the diagnosis of bronchiolitis encompasses several diseases with distinct underlying mechanisms, considerable heterogeneity in treatment responses, and ultimately different therapeutic targets. Understanding this heterogeneity may be the only way to deliver appropriate, stratified treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
0
23
0
2
Order By: Relevance
“…In addition, the recent understanding of asthma not as a disease with a single mechanism of illness but as a syndrome [ 23 , 24 ], reformulates our interpretation of causality previously ascribed to RSV, demanding a recategorization of the specific relationship between “RSV bronchiolitis” and the several different “asthmas” experienced during childhood [ 25 ]. In this review, we summarize the literature exploring the association between RSV LRTI in infancy and subsequent recurrent wheezing and pediatric asthma.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the recent understanding of asthma not as a disease with a single mechanism of illness but as a syndrome [ 23 , 24 ], reformulates our interpretation of causality previously ascribed to RSV, demanding a recategorization of the specific relationship between “RSV bronchiolitis” and the several different “asthmas” experienced during childhood [ 25 ]. In this review, we summarize the literature exploring the association between RSV LRTI in infancy and subsequent recurrent wheezing and pediatric asthma.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we defined bronchiolitis as first respiratory distress with or without wheezing associated with a lower respiratory tract infection at the age under 12 months. Unfortunately, there is not a universally accepted consensus of the diagnosis of bronchiolitis, which means that bronchiolitis includes a heterogeneous group of diseases . Earlier, a large multicentre study from the United States and Finland has observed four profiles of bronchiolitis patient at the age under 24 months, which indicates the heterogeneity of bronchiolitis diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is not a universally accepted consensus of the diagnosis of bronchiolitis, which means that bronchiolitis includes a heterogeneous group of diseases. 23 Earlier, a large multicentre study from the United States and Finland has observed four profiles of bronchiolitis patient at the age under 24 months, which indicates the heterogeneity of bronchiolitis diagnosis. 24 Those profiles differ by causative virus, earlier history of wheezing and eczema, current wheezing, age on admission and the severity of the disease.…”
mentioning
confidence: 97%
“…A candidate from NIAID-Sanofi with an NS2 non-structural protein deletion that reduces viral suppression of the interferon response and increases the innate immune response has advanced in parallel with a second NIAID-Sanofi candidate with a deletion in the RSV M2-2 protein attenuating viral replication while upregulating gene transcription and antigen expression (NCT02237209 and NCT02040831) 57– 62 . These candidates appear mildly over- and under-attenuated, respectively 61 . Vectored approaches for children include Ad26.RSV.preF using a human adenovirus 26 now in phase 2 trials in adults and 12- to 24-month-old RSV seropositive toddlers (NCT03303625) 63, 64 and ChAd155-RSV (NCT02927873) 65 , a replication-incompetent chimpanzee adenovirus 155 now in phase 2 in seropositive children.…”
Section: Surge Of Approaches To Prevent Respiratory Syncytial Virus Lmentioning
confidence: 97%